Engineering human epidermal growth receptor 2‑Targeting hepatitis B virus core nanoparticles for siRNA delivery in vitro and in vivo - Mohamed Suffian, Izzat Fahimuddin; Wang, Julie Tzu-Wen; Faruqu, Farid Nazer; Benitez, Julio; Nishimura, Yuya; Ogino, Chiaki; Akihiko, Kondo; Al-Jamal, Khuloud (American Chemical Society, 2018)
Hepatitis B virus core (HBc) particles acquire the capacity to disassemble and reassemble in a controlled manner, allowing entrapment and delivery of drugs and macromolecules to cells. HBc particles are made of 180−240 copies of 21 kDa protein monomers, assembled into 30−34 nm diameter icosahedral particles. In this study, we aimed at formulating HBc particles for the delivery of siRNA for gene silencing in vitro and in vivo. We have previously reported recombinant HBc particles expressing ZHER2 affibodies, specifically targeting human epidermal growth receptor 2 (HER2)-expressing cancer cells (ZHER2-ΔHBc). siRNA was encapsulated within the ZHER2-ΔHBc particles following disassembly and reassembly. The ZHER2-ΔHBc−siRNA hybrids were able to secure the encapsulated siRNA from serum and nucleases in vitro. Enhanced siRNA uptake in HER2-expressing cancer cells treated with ZHER2-ΔHBc−siRNA hybrids was observed compared to the nontargeted HBc−siRNA hybrids in a time- and dose-dependent manner. A successful in vitro pololike kinase 1 (PLK1) gene knockdown was demonstrated in cancer cells treated with ZHER2-ΔHBc−siPLK1 hybrids, to levels comparable to commercial transfecting reagents. Interestingly, ZHER2-ΔHBc particles exhibit intrinsic capability of reducing the solid tumor mass, independent of siPLK1 therapy, in an intraperitoneal tumor model following intraperitoneal injection.